Crystal structure of human METTL6, the m3C methyltransferase - Ran Chen (Nature Portfolio, 2021)
Ran Chen et al. report the crystal structure of human m3C methyltrasfease METTL6. They generate structure models of hMETTL6 in complex with substrates, providing important insight into the molecular recognition mechanism by METTL6 and may aid in the METTL-based rational drug design in the future.